Hydration Characteristics of Cement Paste Containing Supplementary Cementitious Materials - Elahi, A.; Khan, Q.; Barbhuiya, Salim; Basheer, P.; Russell, M. (Springer, 2012)
An experimental investigation was carried out to evaluate the hydration characteristics and compressive strength development of cement paste containing various supplementary cementitious materials (SCMs), viz. pulverised fuel ash (PFA), ground granulated blast-furnace slag (GGBS) and microsilica (MS). Cement pastes were prepared in two series (A and B). Mixes of series A were manufactured with a fixed water–binder ratio of 0.30 and a superplasticiser, whereas the water–binder ratios of mixes in series B were equivalent to those needed for standard consistencies. The XRD and TG data showed that the addition of PFA, GGBS and MS reduced the intensity of Ca(OH)2 peaks at test ages of 3, 7, 28 and 91 days. The incorporation of PFA and GGBS in the cement paste mixes produced a lower strength value at early age. However, at later ages, the strength was either greater or comparable to the control specimen. Although the compressive strength of cement paste containing 15% MS was greater than that of the PFA and GGBS pastes at all ages, from a cost point of view, it can be suggested that combinations of 40% PFA and 7.5% MS or 50% GGBS and 7.5% MS may be best to improve the hydration properties and compressive strength of cement paste.